A Patient with HIV Treated with Ipilimumab and Stereotactic Radiosurgery for Melanoma Metastases to the Brain. (8th December 2013) - Ruzevick, Jacob; Nicholas, Sarah; Redmond, Kristin; Kleinberg, Lawrence; Lipson, Evan J.; Lim, Michael
Abstract : Cancers, such as melanoma, that are associated with immune deficiencies are a major cause of morbidity and mortality in HIV-infected patients. Once patients develop melanoma metastases to the brain, treatment is often limited to palliative surgery and/or radiation. Ipilimumab, a CTLA-4 antagonist, has been shown to improve the median survival of patients with metastatic melanoma. However, available data regarding the safety and efficacy of ipilimumab in HIV-infected patients who develop intracranial melanoma metastases is limited. Here we report our experience administering ipilimumab to a patient with HIV-AIDS who developed multiple intracranial melanoma metastases. Following treatment, our patient showed improvement in systemic tumor control without any apparent interference with antiretroviral treatment.